Physics-informed deep learning model for predicting outdoor temperature field incorporating building anthropogenic heat emission - Xiang Zhu; Haonan Lin; Xiaoqing Zhou; Chengliang Fan; Yongbo Cui; Yaru Xu (Building and Environment, 2026)

Energetic covalent organic frameworks integrating ionic polynitrogen and fluorine or nitro groups for high detonation performance - Jin Zhu; Haonan Lin; Shunxiang Qin; Fanglin Li; Shuyue Xu; Longyi Zhu; Hua Qian (Chemical Engineering Journal, 2026)

Materials-centric protein corona design in polyurethanes for pro-regenerative immune modulation and soft tissue repair - Jingjing Lin; Mingtao Luo; Haonan Qi; Xue Wu; Junhong Li; Yuan Feng; Zhen Li; Feng Luo; Jiehua Li; Hong Tan; Ting Lan; Yanchao Wang (Chemical Engineering Journal, 2026)

Heterodimeric prodrug nanoassembly overcomes chemoresistance and ignites immunotherapy in glioblastoma - Guanting Li; Shunzhe Zheng; Penghui Wei; Haonan Li; Meixiu Lu; Xuegang Niu; Jiebo Li; Huimin Wang; Wen Huang; Chenyu Ding; Yuanxiang Lin; Yang Zhu; et al. (Chemical Engineering Journal, 2026)

Effects of thermal environment on sleep quality and comfort: Neurophysiological evidence from sleep microstructure - Haonan Ma; Guodan Liu; Shuang Zhang; Yulei Lin; Shuxuan Li; Xuemin Du; Mingli Lu; Songtao Hu (Building and Environment, 2026)

Dynamic changes in volatile organic compounds and microbial community of snakehead segments coated with a gallic acid–embedded edible film - Hongyu Jiang; Wang Li; Haonan Gong; Enhao Yao; Chaofan Ji; Xinping Lin; Beiwei Zhu; Sufang Zhang (Food Research International, 2026)

Polycyclic aromatic hydrocarbons-induced suppression of the PPARα/ACAA1 axis drives hepatic steatosis: Integrating epidemiology, network toxicology, and experimental validation - Haonan Cui; Peng Zou; Wang Yang; Shijun He; Jinyuan Shi; Ting Sun; Mengge Wang; Zhiyong Song; Hanni Guan; Tong Wang; Lei Sun; Qing Chen; et al. (Chemico-Biological Interactions, 2026)

The role of KPNA3 in multiple myeloma: implications for targeting nuclear import - Hongmei Luo; Ziyue Mi; Jingcao Huang; Jingjing Wen; Siyao He; Haonan Yang; Yue Zhang; Linfeng Li; Xiang Liu; Xinyu Zhai; Fangfang Wang; Xinai Gan; et al. (Apoptosis, 2026)

Mo and S Co-doped Cu-BTC as an efficient catalyst for H2O2 activation to eliminate sulfadiazine through a singlet oxygen dominated non-radical pathway - Haonan Shen; Hangjie Chen; Fan Chen; Simeng Xia; Zhou Shi; Lin Deng; Haojie Zhang (Journal of Environmental Chemical Engineering, 2026)

Weathering-induced lithium mineralization on granite in South China: Li-rich muscovite accumulation and cookeite neoformation - Haonan Zhao; Kunyue Ling; Yi Cao; Xuefei Liu; Lin Xu; Shuilong Wang; Wenbin Yu; Hanjie Wen (Applied Clay Science, 2026)

Leaf spot disease on Viburnum odoratissimum caused by Corynespora cassiicola and Colletotrichum species in China - Feng Lin; Xiaojie Peng; Kai Cai; Haonan Wang; Lifeng Zhou; Xudong Zhou (Crop Protection, 2026)

Human umbilical cord MSC-derived exosomes attenuate radiation-induced pulmonary fibrosis via remodeling the gut-lung axis in mice - Yan Zhou; Haonan Wang; Ling Guo; Xiaodie Liu; Xing Wang; Yue Liu; Mengjuan Shang; Bo Zheng; Kewei Li; Lin Liu; Jing Li; Guirong Ding (Life Sciences in Space Research, 2026)

Structural diversity of aldehydes determines covalent versus non-covalent inhibition mechanisms against steroid 5α-reductase type 1: Species-specific differences and preliminary structure-activity relationships - Junying Chen; Shufang Qi; Zijian Lin; Haonan Fang; Putian Zhang; Wanyu Li; Ren-shan Ge; Yiyan Wang (Chemico-Biological Interactions, 2026)

Application of physics-informed neural networks-based hybrid prediction models in campus thermal environment prediction - Yongbo Cui; Xiaoqing Zhou; Chengliang Fan; Haonan Lin; Simin Deng (Building and Environment, 2026)

Lactobacillus johnsonii JJB3 Ameliorates Oxidative Stress-Induced Intestinal Injury and Mitochondrial Damage by Promoting BNIP3L-Mediated Mitophagy - Xingmei Liu; Jinge Xin; Ning Sun; Yuhua Qin; Haonan Huang; Benhao Chen; Lixiao Duan; Yanxi Zhou; Dandan Wang; Bo Jing; Yan Zeng; Dong Zeng; et al. (Probiotics and Antimicrobial Proteins, 2026)

Corrigendum to “boosting sustainable monocyclic aromatics yield from catalytic fast pyrolysis of cotton stalk via a novel ZnZrOx-ZSM-5 tandem catalysis” [Chem. Eng. J. Volume 524, 15 November 2025, 168988] - Lingxi Bai; Haonan Li; Xingxiang Wang; Xin Pu; Zhipeng Lin; Shuzhen Zhou; Jiangbing Li; Xiaogang Wang; Jie Li; Lingtao Kong; Lanli Bai; Jichang Liu (Chemical Engineering Journal, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Boosting sustainable monocyclic aromatics yield from catalytic fast pyrolysis of cotton stalk via a novel ZnZrOx-ZSM-5 tandem catalysis - Lingxi Bai; Haonan Li; Xingxiang Wang; Xin Pu; Zhipeng Lin; Shuzhen Zhou; Jiangbing Li; Xiaogang Wang; Jie Li; Lingtao Kong; Lanli Bai; Jichang Liu (Chemical Engineering Journal, 2025)

Mulberry (Morus alba L.) planting increased the abundance of soil carbon cycling functional genes by improving soil properties, and further enhanced the stability of soil carbon pool - Meina Zhu; Zi Yang; Zhenjiang Wang; Victor Edem Tsigbey; Zipei Cui; Wenfeng Zhang; Weijun Zhu; Jianbin Li; Changyu Qiu; Qiang Lin; Haonan Li; Hanfa Shahid; et al. (Plant and Soil, 2025)

Predicting arsenic bioaccessibility: A global data-driven machine learning approach and its implication for reducing carbon emissions - Haonan Zhang; Dan Han; Maosheng Zhong; Tianxiang Xia; Suo Yang; Shijie Wang; Ping Zhang; Lin Jiang (Journal of Hazardous Materials, 2025)

Simulation-guided plasma surface engineering for enhanced triboelectric Nanogenerator performance - Hong Yu; Haonan Ma; Zuying Huang; Mengya Lin; Junming Chen; Ruibin Wu; Ye Tao; Chengrun Li; Ruijia Yang; Xiaozhen Du (Chemical Engineering Journal, 2025)

Letter to the editor: Comments on “Microplastic polyethylene induced inner ear dysfunction in murine model” - Haonan Lin; Liming Shang; Lexin Wang; Ke Xu (Journal of Hazardous Materials, 2025)

A dual-dynamic crosslinking network enabled strong, flexible, self-healing, and biodegradable chitosan fiber paper/vitrimer composites for plastic substitution - Xiaoqian Zhang; Leyi Lin; Haonan Zhou; Jie Zou; Wang Zhao; Guowen Zhou; Zepeng Lei; Xiaohui Wang (Carbohydrate Polymers, 2025)

Research on recognition of bedding system coverage rate using infrared thermal imaging - Haonan Ma; Guodan Liu; Yulei Lin; Guodong Zhu; Peiqi Zhang; Mingli Lu; Songtao Hu (Journal of Thermal Biology, 2025)

Quality assessment and microbial community succession of finely chopped common carp (Cyprinus carpio) under low-temperature storage: Implications for nutritional composition and spoilage indicators - Haonan Gong; Binchen Wang; Hongyu Jiang; Wang Li; Yujiao Zhang; Chaofan Ji; Xinping Lin; Sufang Zhang (Food Control, 2025)

Strong thermospheric response to the almost undetectable substorm on May 29, 2023 - Yongliang Zhang; Qian Wu; Wenbin Wang; Larry Paxton; Robert Schaefer; Dong Lin; Lying Qian; Haonan Wu; Kun Wu; Ying Zou; Martin Connors (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Effect of oxidation on finely segmented products of snakehead: Digestibility and microstructure - Hongyu Jiang; Wang Li; Haonan Gong; Chaofan Ji; Xinping Lin; Beiwei Zhu; Sufang Zhang (Food Chemistry, 2025)

Pulmonary surfactant biogenesis blockage mediated polyhexamethylene guanidine disinfectant induced pulmonary fibrosis - Xin Li; Jianzhong Zhang; Mingyue Wang; Haonan Li; Wanjun Zhang; Jiayin Sun; Lin Zhang; Yuxin Zheng; Jing Liu; Jinglong Tang (Journal of Hazardous Materials, 2024)

Input panel for handwriting detection based on triboelectric nanogenerator - Zhigang Peng; Wandi Chen; Jianpu Lin; Haonan Wang; Heng Tang; Yu Zhang; Tailiang Guo; Xiongtu Zhou; Chaoxing Wu; Yongai Zhang (Chemical Engineering Journal, 2024)

A preliminary study of T-2 toxin that cause liver injury in rats via the NF-kB and NLRP3-mediated pyroptosis pathway - Shicong Zheng; Haonan Li; Hexuan Dong; Fang Qi; Bing Zhang; Qian Yu; Buyi Lin; Hong Jiang; Haoyu Du; Ying Liu; Jun Yu (Toxicon, 2024)

Multi-phase SPH-FDM and experimental investigations on the hydrodynamics of an oscillating water column wave energy device - Fang He; Haonan Jiang; Yuan Lin; Jiapeng Pan; Yifan Zhang; Can Huang (Coastal Engineering, 2024)

Unraveling the mechanisms and responses of aniline-degrading biosystem to salinity stress in high temperature condition: Pollutants removal performance and microbial community - Qi He; Qian Zhang; Junhao Su; Meng Li; Bing Lin; Nanping Wu; Haonan Shen; Jiajing Chen (Chemosphere, 2024)

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

Polymer composite membranes as SERS substrate materials: Recyclable and highly stable - Haonan Wang; Chuyi Wang; Qingling Nie; Ru Liu; Yixuan Yang; Jiayi Lin; Bohan Zhang; Ruiyun You; Yunzhen Liu; Xiufeng Xiao; Yudong Lu (Chemical Engineering Journal, 2024)

Fenton-like system of UV/Glucose-oxidase@Kaolin coupled with organic green rust: UV-enhanced enzyme activity and the mechanism of UV synergistic degradation of photosensitive pollutants - Xiangyu Liu; Lei Zhang; Qian Zhang; Meng Li; Ziqi Zhao; Bing Lin; Jie Peng; Haonan Shen; Qi He (Environmental Research, 2024)

Research on satellite data-driven algorithm for ground-level ozone concentration inversion: case of Yunnan, China - Weiqiang Yu; Tao Feng; Xingwei Man; Huan Lin; Haonan Zhang; Rui Liu (Earth Science Informatics, 2024)

All-natural chitosan-based polyimine vitrimer with multiple advantages: A novel strategy to solve nondegradable plastic waste pollution - Xiaoqian Zhang; Leyi Lin; Haonan Zhou; Guowen Zhou; Xiaohui Wang (Journal of Hazardous Materials, 2024)

Association of urinary polycyclic aromatic hydrocarbon metabolites with gestational diabetes mellitus and gestational hypertension among pregnant women in Southwest China: A cross-sectional study - Dengqing Liao; Shimin Xiong; Songlin An; Lin Tao; Lulu Dai; Yingkuan Tian; Wei Chen; Caidie He; Pei Xu; Nian Wu; Xiang Liu; Haonan Zhang; et al. (Environmental Pollution, 2024)

Perturbation of IP3R-dependent endoplasmic reticulum calcium homeostasis by PPARδ-activated metabolic stress leads to mouse spermatocyte apoptosis: A direct mechanism for perfluorooctane sulfonic acid-induced spermatogenic disorders - Wang Yang; Xi Ling; Shijun He; Haonan Cui; Lihong Wang; Zeyu Yang; Huihui An; Peng Zou; Qing Chen; Lei Sun; Huan Yang; Jinyi Liu; et al. (Environmental Pollution, 2024)

Mercury pollution risks of agricultural soils and crops in mercury mining areas in Guizhou Province, China: effects of large mercury slag piles - Chengcheng Zhang; Tianxiang Xia; Lina Zhang; Zhuo Chen; Haonan Zhang; Xiaoyang Jia; Lin Jia; Xiaoying Zhu; Guangbing Li (Environmental Geochemistry and Health, 2024)

Numerical research on hydrodynamic characteristics of the disk-shaped autonomous underwater vehicle near free surface - Jin Guo; Yuan Lin; Ying Wang; Peiwen Lin; Haonan Li; Haocai Huang; Ying Chen (Ocean Engineering, 2023)

Elucidating the roles of Cr(VI)-Cu(II) Co-pollution in the stress of aniline degradation stress: Insights into metabolic pathways and functional genes - Bing Lin; Bin Tan; Xiangyu Liu; Meng Li; Haojin Peng; Qian Zhang; Jiajing Chen; Haonan Shen; Qi He (Bioresource Technology, 2023)

Heat source model for Enhanced Geothermal Systems (EGS) under different geological conditions in China - Wenjing Lin; Guiling Wang; Haonan Gan; Shengsheng Zhang; Zhen Zhao; Gaofan Yue; Xiting Long (Gondwana Research, 2023)

TERT transcription and translocation into mitochondria regulate benzo[a]pyrene/BPDE-induced senescence and mitochondrial damage in mouse spermatocytes - Haonan Cui; Wang Yang; Shijun He; Zili Chai; Lihong Wang; Guowei Zhang; Peng Zou; Lei Sun; Huan Yang; Qing Chen; Jinyi Liu; Jia Cao; et al. (Toxicology and Applied Pharmacology, 2023)

Large-scale comparative analysis reveals different bacterial community structures in full- and lab-scale wastewater treatment bioreactors - Yanyan Ma; Dongni Rui; Haonan Dong; Xuxiang Zhang; Lin Ye (Water Research, 2023)

Experimental investigation of steel fiber reinforced concrete slabs subjected to underwater contact explosions - Haonan Zhao; Xiaohua Zhao; Hongyuan Fang; Lin Yang; Jinshan Sun; Shucan Liu; Zhidong Liu (Ocean Engineering, 2023)

Sewage Sludge-Derived catalyst for extremely efficient electrocatalytic elimination of organic pollutants in water - Haonan Zhang; Shaoqing Chen; Nianji Zhang; Huihuang Chen; Yutong Yang; Yang Tu; Chuanlai Jiao; Zian Xu; Yu Xia; Hongri Suo; Zesheng Li; Chongxuan Liu; et al. (Chemical Engineering Journal, 2023)

Human Serum Albumin-enriched Clopidogrel Bisulfate Nanoparticle Alleviates Cerebral Ischemia–Reperfusion Injury in Rats - Yiting Luo; Yunli Xia; Haonan Zhang; Yunzhu Lin; Lili He; Tao Gong; Zhirong Zhang; Li Deng (Pharmaceutical Research, 2023)

Enhanced selective separation of vanadium(V) and chromium(VI) using the CeO2 nanorod containing oxygen vacancies - Ruixi Lin; Jiarong Li; Xuequan Jing; Meina Guo; Guoqing Ren; Haonan Qin; Zhangwei Yao; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; et al. (Environmental Science and Pollution Research, 2023)

Enhanced adsorption of bio-oil on activated biochar in slurry fuels and the adsorption selectivity - Shanshan Yan; Haoran Chen; Haonan Zhu; Zixiang Lin; Gang Wu; Wenran Gao; Hong Zhang; Xun Hu; Junjie Zhang; Shu Zhang; Shoujun Zhang; Yinlong Wu (Fuel, 2023)

Spatiotemporal analysis and prediction of water quality in Pearl River, China, using multivariate statistical techniques and data-driven model - HaoNan Ding; Xiaojun Niu; Dongqing Zhang; Mengyu Lv; Yang Zhang; Zhang Lin; Mingli Fu (Environmental Science and Pollution Research, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

A high-efficient anisotropic continuum model for the optimization of heat transfer and chemical reaction in a packed-bed water gas shift reactor - Bo Jiang; Haonan Wang; Kewei Yu; Jing Ma; Wang Si-ma; Yuming Gao; Lin Li; Xinwei Zhang; Huiru Cui; Dawei Tang (Fuel, 2023)

Effects of exposure to phthalate during early pregnancy on gestational diabetes mellitus: a nested case–control study with propensity score matching - Wei Chen; Caidie He; Xiang Liu; Songlin An; Xia Wang; Lin Tao; Haonan Zhang; Yingkuan Tian; Nian Wu; Pei Xu; Dengqing Liao; Juan Liao; et al. (Environmental Science and Pollution Research, 2022)

Development of a pressure-retaining separation and transfer system for sediment and overlying seawater - Jin Guo; Qixiao Zhou; Yongqiang Ge; Haonan Li; Qiaoling Gao; Ying Wang; Yuan Lin; Jiawang Chen (Frontiers in Marine Science, 2022)
Methane leakage at the interface between sediment and overlying seawater is an important basis for gas hydrate exploration. Therefore, a transfer device with working pressure of 30MPa and corresponding scheme are proposed to separate and transfer the sediment and overlying water inside the sampler under the condition of pressure-retaining. Based on the pressure relief valve with adjustable threshold pressure, the device transfers the overlying water by compressing the internal volume and transfers the sediment by secondary sampling. The performance of transfer device is studied by simulation and experiment. Based on the coupled Eulerian-Lagrangian approach in the Abaqus, the secondary sampling was investigated, and the penetration resistance and coring rate of the secondary sampling tube are 141N and 86.2%, respectively. By using the hydraulic simulation software AMESim, the pressure fluctuation caused by the movement of the mechanism during the transfer process was studied, and the pressure fluctuation amplitude is within 0.89 MPa. Furthermore, the laboratory transfer tests were carried out under high pressure conditions, and meantime, the simulation results are verified. Under the working condition of 30MPa, the device can maintain a pressure loss of no more than 8.0% (2.4MPa) within two hours, maintain pressure fluctuations during the transfer process within 4.8% (1.44MPa), and ensure that the pressure in the culture kettle decreases by 4.7% relative to the pressure in the sampler after the transfer, which shows the feasibility of the device application.

Study on the Motion Stability of the Autonomous Underwater Helicopter - Yuan Lin; Jin Guo; Haonan Li; Hai Zhu; Haocai Huang; Ying Chen (Journal of Marine Science and Engineering, 2022)
The hydrodynamic performance of a novel hovering autonomous underwater vehicle, the autonomous underwater helicopter (AUH), with an original disk-shaped hull (HG1) and an improved fore–aft asymmetric hull (HG3), is investigated by means of computational fluid dynamics with the adoption of overlapping mesh method. The hydrodynamic performance of the two hull shapes in surge motion with variation of the angle of attack is compared. The results show that HG3 has less resistance and higher motion stability compared to HG1. With the angle of attack reaching 10 degrees, both HG1 and HG3 achieve the maximum lift-to-drag ratio, which is higher for HG3 compared to HG1. Furthermore, based on the numerical simulation of the plane motion mechanism test (PMM) and according to Routh’s stability criterion, the horizontal movement and vertical movement stability indexes of HG1 and HG3 (GHHG1=1.0, GVHG1=49.7, GHHG2=1.0, GVHG3=2.1) are obtained, which further show that the AUH has better vertical movement stability than the torpedo-shaped AUV. Furthermore, the scale model tail velocity experiment indirectly shows that HG3 has better hydrodynamic performance than HG1.

Screening of three Chlorella mutant strains with high lipid production induced by 3 types of lasers - Kang Wang; Bin Lin; Chunxiao Meng; Zhengquan Gao; Zhe Li; Haonan Zhang; Huanmin Du; Fei Xu; Xiao Jiang (Journal of Applied Phycology, 2020)

Plant growth regulators affect biomass, protein, carotenoid, and lipid production in Botryococcus braunii - Huanmin Du; Jiali Ren; Zhe Li; Haonan Zhang; Kang Wang; Bin Lin; Shanmin Zheng; Changyu Zhao; Chunxiao Meng; Zhengquan Gao (Aquaculture International, 2020)

A thiopyran derivative with low murine toxicity with therapeutic potential on lung cancer acting through a NF-κB mediated apoptosis-to-pyroptosis switch - Liping Chen; Bixia Weng; Huimin Li; Haonan Wang; Qian Li; Xiaoyan Wei; Hui Deng; Sicen Wang; Chengxi Jiang; Renyu Lin; Jianzhang Wu (Apoptosis, 2019)